SARS-CoV2 Infection During Pregnancy Causes Persistent Immune Abnormalities in Women Without Affecting the Newborns - Vazquez-Alejo, Elena; Tarancon-Diez, Laura; Carrasco, Itzíar; Vigil-Vázquez, Sara; Muñoz-Chapuli, Mar; Rincón-López, Elena; Saavedra-Lozano, Jesús; Santos-Sebastián, Mar; Aguilera-Alonso, David; Hernanz-Lobo, Alicia; Santiago-García, Begoña; de León-Luis, Juan Antonio; et al. (Frontiers in Immunology, 2022)
SARS-CoV2 infection in pregnancy and exposed newborns is poorly known. We performed a longitudinal analysis of immune system and determined soluble cytokine levels in pregnant women infected with SARS-CoV2 and in their newborns. Women with confirmed SARS-CoV2 infection and their exposed uninfected newborns were recruited from Hospital Gregorio Marañón. Peripheral blood mononuclear cells (PBMCs), cord cells and plasma were collected at birth and 6 months later. Immunophenotyping of natural killer (NK), monocytes and CD4/CD8 T-cells were studied in cryopreserved PBMCs and cord cells by multiparametric flow cytometry. Up to 4 soluble pro/anti-inflammatory cytokines were assessed in plasma/cord plasma by ELISA assay. SARS-CoV2-infected mothers and their newborns were compared to matched healthy non-SARS-CoV2-infected mothers and their newborns. TNFα and IL10 levels were increased at baseline in SARS-CoV2 infected mothers. Infected mothers showed increased NK cells activation and reduced expression of maturation markers that reverted after 6 months. Infected mothers had high frequency of Central Memory and low Effector Memory CD4-T cells subsets; CD4-T and CD8-T cells showed high levels of activation (HLA-DR/CD38) and exhaustion (TIM3/TIGIT) at baseline and remained elevated 6 months later. Treg levels were lower at infected mothers at baseline but reverted after 6 months. No newborn was infected at birth, but those from SARS-CoV2 infected mothers had decreased NK, monocytes and CD4 T-cells that significantly increased 6 months later. Conclusions: SARS-CoV2 infection during pregnancy shows differences in immunological components that could lead newborns to future clinical implications after birth. However, SARS-CoV2 exposed 6-months-old showed no immune misbalance, whereas infected mothers maintain increased activation and exhaustion levels in T-cell after 6 months.